The big fix : 7 practical steps to save our planet - Harvey, Hal; Gillis, Justin; Silberg, Mark; Myers, Amanda (Simon & Schuster, 2022)
"An engaging, accessible citizen's guide to the seven urgent changes that will really make a difference for our climate-and how we can hold our governments accountable for putting these plans into action. Dozens of kids in Montgomery County, Maryland, agitated until their school board committed to electric school buses. Mothers in Colorado turned up in front of an obscure state panel to fight for clean air. If you think the only thing you can do to combat climate change is to install a smart thermostat or cook plant-based burgers, you're thinking too small. That's where The Big Fix comes in, offering everyday citizens a guide to the seven essential changes our communities must enact to bring our greenhouse gas emissions down to zero-and sharing stories of people who are making those changes reality. Energy policy advisor Hal Harvey and longtime New York Times reporter Justin Gillis hone in on the seven areas where ambitious but eminently practical changes will have the greatest effect: electricity production, transportation, buildings, industry, urbanization, use of land, and investment in promising new green technologies. In a lively, jargon-free style, the pair illuminate how our political economy really works, revealing who decides everything from what kind of power plants to build to how efficient cars must be before they're allowed on the road to how much insulation a new house requires-and how we can insert ourselves into all these decisions to ensure that the most climate-conscious choices are being made. At once pragmatic and inspiring, The Big Fix is an indispensable action plan for citizens looking to drive our country's greenhouse gas emissions down to zero-and save our climate"--